Manuels utilisés dans l'enseignement de la langue dans les écoles à pédagogie convergente: disponibilité et utilisatio (Nordic Journal of African Studies, 2000)
This article looks at the use of text books in French and national languages in the type of bilingual education known as convergent pedagogy, which is now the official educational programme in Mali. Based on two field trips to Ségou in 1999, it gives the views of pupils, teachers and directors as expressed in interviews and questionnaires, and combines this with classroom observation. It suggests that though important additional funding is needed, the situation might be improved by a more efficient distribution chain at all levels and also by a more judicious choice of books for the class libraries. This includes more books in the national languages, for though the official policy is balanced bilingual teaching, French fares better in every way : the national language textbooks are fewer, distributed in smaller numbers, and come without teachers’ guidebooks. One should thus start with the production of more textbooks in national languages.